Occupational syncarcinogenesis in the skin: combined effects of two carcinogens from the German occupational disease list - Dickel, Heinrich; Bruckner, Thomas (Journal der Deutschen Dermatologischen Gesellschaft, 2016)
Background Though scientifically undisputed, cutaneous syncarcinogenesis is not reflected in German occupational disease (OD) regulations, which tend to be guided by the tenet of monocausality. Recognition of nonmelanoma skin cancer (NMSC) and its precursor lesions as OD requires individual assessment as to whether the requirements pursuant to either OD 5103 (occupational exposure to natural UV radiation) or OD 5102 (occupational exposure to polycyclic aromatic hydrocarbons) are fulfilled. Methods Retrospective analysis of 28 patients (median age 72.5 years) with NMSC and respective precursor lesions who had been occupationally exposed to natural UV radiation and polycyclic aromatic hydrocarbons. All cases had undergone expert medical assessment between September 2012 and September 2015. Results According to our assessments, all 28 cases met the occupational requirements pursuant to OD 5103 and 5102. In 26 cases (93 %), we recommended recognition of skin cancer as occupational disease pursuant to both OD 5103 and OD 5102. The competent occupational insurance association (BG) followed our recommendation in four cases. In eight cases, recognition was solely based on OD 5103; in ten cases, only on OD 5102. Four cases were denied recognition. Conclusions Following adequate cumulative occupational exposure to natural UV light as well as occupational exposure to polycyclic aromatic hydrocarbons, NMSC or its precursor lesions arising in UV-exposed areas should be reported to the competent occupational insurance association as “OD 5103 and 5102 in terms of syncarcinogenesis”. Apart from the fact that the ensuing recognition proceedings will be able to more adequately reflect real-life workplace conditions, filing a report pursuant to both ODs also allows for recognition of basal cell carcinoma as occupational disease. According to current regulations, this would not be possible, if the assessment were solely based on OD 5103.